Gregariousness, foraging effort, and affiliative interactions in lactating bonobos and chimpanzees. (23rd December 2020) - Lee, Sean M; Hohmann, Gottfried; Lonsdorf, Elizabeth V; Fruth, Barbara; Murray, Carson M
Abstract: Fission–fusion dynamics have evolved in a broad range of animal taxa and are thought to allow individuals to mitigate feeding competition. While this is the principal benefit of fission–fusion, few studies have evaluated its costs. We compared gregariousness, foraging budgets, and social budgets between lactating bonobos and chimpanzees from wild populations to evaluate potential costs. Both species exhibit fission–fusion dynamics, but chimpanzees, particularly in East African populations, appear to experience higher feeding competition than bonobos. We expected lactating chimpanzees to be less gregarious than lactating bonobos; reduced gregariousness should allow lactating chimpanzees to mitigate the costs of higher feeding competition without requiring more foraging effort. However, we expected the reduced gregariousness of lactating chimpanzees to limit their time available for affiliative interactions. Using long-term data from LuiKotale bonobos and Gombe chimpanzees, we found that lactating chimpanzees were indeed less gregarious than lactating bonobos, while feeding and travel time did not differ between species. Contrary to our predictions, lactating females did not differ in social interaction time, and lactating chimpanzees spent proportionately more time interacting with individuals other than their immature offspring. Our results indicate that lactating chimpanzees can maintain social budgets comparable to lactating bonobos despite reduced gregariousness and without incurring additional foraging costs. We discuss potential explanations for why lactating bonobos are more gregarious. Abstract : In some group-living species, individuals divide into subgroups to minimize feeding competition, which can reduce social opportunities. Bonobos and chimpanzees exhibit such dynamics, but chimpanzees face higher feeding competition and can spend substantial time feeding alone. Despite this difference in grouping, females of the two species spend similar amounts of time engaged in social interactions.